INTERACTIVE MULTIMEDIA USE TO INCREASE LEARNING INTEREST - Anggi Tiarasari Tiarasari; Sukarno Sukarno; Sarwanto Sarwanto (Universitas Sebelas Maret, 2018)
This paper aims to describe the use of interactive multimedia to enhance interest in learning. Innovative learning media is very important in achieving the learning process. But there are still many teachers who have not literacy will use the latest technology. Therefore, the need for the latest innovations on interactive multimedia. This study uses literature study. Library study is an activity to collect information relevant to the topic or problem that becomes the object of research. Based on literature review shows that not many teachers who use interactive multimedia in learning in the class so that student learning interest is low. Conclusions based on literature review an alternative effort to improve the use of innovative learning media is to create interactive multimedia on learning